2013
DOI: 10.1080/08927014.2013.847926
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of biofouling using electromagnetic fields in tubular heat exchangers–condensers cooled by seawater

Abstract: Electromagnetic field (EMF) treatment is presented as an alternative physical treatment for the mitigation of biofouling adhered to the tubes of a heat exchanger-condenser cooled by seawater. During an experimental phase, a fouling biofilm was allowed to grow until experimental variables indicated that its growth had stabilised. Subsequently, EMF treatment was applied to seawater to eliminate the biofilm and to maintain the achieved cleanliness. The results showed that EMFs precipitated ions dissolved in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…Changing from classical to corpuscular quantum physics does not alter this interpretation because the electromagnetic field in the first quantization is treated according to Maxwell's equations, implying continuous waves and not as quantized photons. Previous literature (Trueba et al, 2014;Cellini et al, 2008;Chua and Yea, 2005;Del re et al, 2004) reveals a sensitivity of living organisms to very weak electromagnetic fields. One has to consider how liquid water would react to a quantized virtual electromagnetic field known to be present in the vacuum generated through H-bonding between water molecules Del Guidice et al, 2010).…”
Section: Detection Of Electrical Signals and Water Sensitivity To Elementioning
confidence: 97%
See 3 more Smart Citations
“…Changing from classical to corpuscular quantum physics does not alter this interpretation because the electromagnetic field in the first quantization is treated according to Maxwell's equations, implying continuous waves and not as quantized photons. Previous literature (Trueba et al, 2014;Cellini et al, 2008;Chua and Yea, 2005;Del re et al, 2004) reveals a sensitivity of living organisms to very weak electromagnetic fields. One has to consider how liquid water would react to a quantized virtual electromagnetic field known to be present in the vacuum generated through H-bonding between water molecules Del Guidice et al, 2010).…”
Section: Detection Of Electrical Signals and Water Sensitivity To Elementioning
confidence: 97%
“…These cations mediate the formation and/or stabilization of the exopolymeric substances matrix network (Tsuneda et al, 2003). In water treated with electromagnetic fields Ca 2þ and Mg 2þ concentrations decrease due to nucleation of ionic calcium or magnesium and their precipitation into calcium or magnesium carbonates (Shahryari and Pakshir, 2008) could influence biofilm growth by acting on the exopolymeric matrix (Trueba et al, 2014). However, no conductivity change was observed between treated and untreated lines in this experiment and ionic strength was approximately 6.2 mM, with 2.4 mM for Ca 2þ and Mg 2þ .…”
Section: Effect Of Emfs In the Presence Of Hydraulic Continuitymentioning
confidence: 99%
See 2 more Smart Citations
“…Trueba et al (2014) reported the mitigation of a mature biofilm formed on the internal surfaces of tubes in a heat exchanger-condenser that used seawater as the refrigerant fluid.…”
Section: Introductionmentioning
confidence: 99%